Doxycycline or Ofloxacin for Outpatient Chlamydial Pelvic Inflammatory Disease? A Cost-Benefit and Cost-Effectiveness Analysis - Michael J. Rosenberg; Michael S. Waugh (Hindawi Limited, 1995)
Objective: The current Centers for Disease Control and Prevention (CDC) guidelines include 2 drugs, doxycycline and ofloxacin, for treatment of the chlamydial component of outpatient pelvic inflammatory disease (PID). Although ofloxacin costs about $90 more than doxycycline, doxycycline is frequently associated with side effects and patient compliance with this drug is probably poor. Because clinicians have little information by which to judge the tradeoffs between price and compliance for these 2 antibiotics, we examined the impact of patient compliance in the evaluation of the costs and benefits of using each drug.